Electrochemical study of heat treated SS304 stainless steel is simulated body fluid - Nik Mohd Nazairen, Nik Cob (2010)
This thesis is entitled about the electrochemical study of heat treated SS304 stainless steel in simulated body fluid environment. Metallic materials are generally used for biomedical devices for various parts of the human body. When a metal device is implanted into human body, it is continually exposed to extracellular tissue fluid. The exposed metal surface of the implant undergoes electrochemical dissolution of material at a finite rate due to the interaction with body environment. This interaction can lead to either failure of the implant or have an adverse effect on the patient resulting in the rejection of the implant by the surrounding tissue or both. In conjunction with that, it is important to improve the corrosion resistance and wear properties by conducting the heat treatment processes. The objectives of this study are, to study the corrosion behaviour of the heat treated SS304 stainless steel in phosphate buffered saline (PBS) and hank’s balanced salt solution (HBSS) as simulated body environment and also to investigate the effect of heat treatment process to the corrosion rate of SS304 stainless steel in PBS and HBSS as simulated body environment. Heat treatment process, which is carburizing has been performed with different temperature and time. Carburizing is a process of adding Carbon to the surface. This is done by exposing the part to a carbon rich atmosphere at an elevated temperature and allows diffusion to transfer the carbon atoms into steel. The electrochemical study was conducted using a potentiostat WPG1000, interfaced to a computer in PBS and HBSS used for simulating human body fluid conditions. SS304 stainless steel show increased in corrosion rate after the carburizing process in simulated body fluid due to the resultant formation of chromium carbides.